The Role of Leadership in Action Research - Thomas G. Ryan (Networks: An Online Journal for Teacher Research, 2001)
The image of a leader is often one of standing alone or above a number of followers. I rejected this traditional image and preferred to stand with others as I led fellow educators through a recent practical action research study. As we began our study the newness of each conversation and the resultant energy made leading somewhat confusing and invisible. Yet, the task of leading was something I could feel every time I looked into a group memberís face. At times the mental replay of this act of looking was a haunting memory and other times it was a source of inspiration. As we pushed through our study I remember feeling annoyed by the fact that our schedule tied me down somewhat as a leader. I was becoming weary at times with the leadership workload. What kept me going was the enthusiasm of the participants who seemed to welcome the adult conversations we had. My goal all along as a leader was to illuminate assessment praxes in a non-evaluative mode of collaborative, participatory action research (McTaggart, 1997). Each of the four participants was joined by a thematic concern to inform and improve assessment. Collectively, these teachers and I chose science as the context in order to examine our current assessment practices.